ANALISIS PENGARUH TEMPERATUR DAN MEDIA PENDINGIN TERHADAP SIFAT KEKERASAN DAN KETANGGUHAN BAJA S45C PADA PISAU CRUSHER - Bagus Ilham Pramudya; Ariyanto Ariyanto; Husman Husman (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
The crusher blade is the part that is used to decompose plastic waste. The crusher blade needs to be worked on to change the mechanical properties of the material to maintain resistance, namely by working on the heat treatment process. In this study, the researcher used steel material with JIS S45C grade of medium steel. Researchers will vary the hardening temperature, namely 800°C, 840°C, 880°C with cooling media using salt water, oil, and sea water. then proceed with the tempering process with a temperature of 500°C. The tests in this research are hardness testing and toughness testing. The purpose of this study is to find the highest optimal value and find out which variables have the most influence on the results. From the results of hardness testing, the highest value is found in salt water with a temperature of 880°C at 36.86 HRC and for toughness testing which has the highest value is found in oil cooling medium with a temperature of 800°C at 1.2015 joule/, and of the two variables that have the most influence on the results of hardness and toughness testing, namely the cooling medium.